Design and Manufacture of a mini-turbojet - Pereira, Rui Gonçalo Gonçalves Esteves (2020)
The development and production of small engines with a jet propulsion system is, relatively recent, taking into account that this type of gas turbine started to be studied and developed many years before the first construction of these small turbojets. However, with the time evolving, the gas turbines turned out to be a greater challenge, becoming more and more difficult to develop and improve. The gas turbine requires an intense study of the several areas related to its functioning, demanding additional knowledge and skill to improve a small detail. Although the detail could be small, the effect on overall performance would be considerable. Until recent times, these small engines were developed without a significant role in the aviation industry, being only used for model jet engines. Even though, in the account of the science evolution, these engines are being studied and prepared to integrate Unmanned Aerial Vehicles, UAV’s, as their propulsion system [1]. This dissertation consists on the development of a turbojet, in a small-scale, respecting the dimensions of the two, previously obtained, components, the compressor, and turbine, from the model turbo IHI RHB31 VZ21. To understand how to execute a design with suitable dimensions, the study of every present component in a turbojet was carried out, in parallel with the fundamental areas, regarding the functioning of a turbojet, such as thermodynamic cycles. At the end of a general study of the turbojet, the author proceeded to the design phase, in which the dimensioning process starts based on the information contained in the various sources of information, found at the bibliography. The dimensioning was carried through by the use of a scale factor. This scale factor was obtained by the compressor’s diameters ratio. In brief, in the Mr.Thomas Kamps’ book, the author advises the novice to divide his compressor diameter by the compressor used for Mr.Kamps’s engine. The diameters ratio, or the scale factor, was applied to the remaining components, produced by Mr.Thomas Kamps,in order to attain the measures for this gas turbine, respecting the recommended. The dimensions of the compressor shroud, inlet flange, diffuser, shaft, shaft housing, combustion chamber, fuel distribution ring, nozzle guide vanes, exhaust nozzle and, the last, outer casing were obtained. The next step was the design process of the referred components, in regard to the observed designs, found in the studied literature, using the three-dimensional design software CATIA V5R18. The design is an empiric process, which reveals itself as extremely difficult to consider one design as absolute. The manufacturing process of the turbojet was executed, at the time, the design process had been concluded. The following action was to acquire the necessary material for the production of the pieces, essentially, aluminum and stainless steel. The aluminum used was cast aluminum, being, then, worked to acquire the requested shape concerning the established design. The majority of the components were manufactured with stainless steel sheets, in which, the pieces were cut, according to their dimensions and shape, in-plane geometry. The chapter describing the manufacture process, as well as, the design process, is explained to allow a future reproduction of the work completed or adaptation for a different compressor/turbine set. Unfortunately, the fabrication of the diffuser and compressor shroud was not possible, since it had extremely small dimensions to be produced in the 5-axis vertical machining center. Moreover, the welding applied to the manufactured pieces was not executed with the required quality, even having increased the material thickness to facilitate the process, as it is explained in chapter 4.3. Therefore, one of the main objectives was not accomplished due to the insufficient means that disabled the manufacture of the jet engine’s parts.